2019
DOI: 10.1002/mc.22990
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of Neuropilin 1 expression by miR‐338‐3p promotes non‐small cell lung cancer via changes in EGFR signaling

Abstract: Neuropilin 1 (NRP1) is a transmembrane glycoprotein that acts as a co‐receptor for multiple extracellular ligands and typically performs growth‐promoting functions in cancer cells. Accumulating evidence indicates that NRP1 is upregulated, and may be an independent predictor of cancer relapse and poor survival, in many cancer types, including non‐small cell lung cancer (NSCLC). Recent evidence suggests that NRP1 affects tumour cell viability via the epidermal growth factor receptor (EGFR) and Erb‐B2 receptor ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Previously, it was demonstrated NRP1 expression in NSCLC tissues and cells was higher than that in adjacent non-cancerous lung tissues and bronchial epithelial cells (22). In this study, to elucidate the role of NRP1 in NSCLC metastasis, NRP1 was stably knocked down in A549 (adenocarcinoma) and H226 (squamous carcinoma) cells.…”
Section: High Expression Of Nrp1 Promotes Nsclc Metastasis In Vitromentioning
confidence: 91%
See 2 more Smart Citations
“…Previously, it was demonstrated NRP1 expression in NSCLC tissues and cells was higher than that in adjacent non-cancerous lung tissues and bronchial epithelial cells (22). In this study, to elucidate the role of NRP1 in NSCLC metastasis, NRP1 was stably knocked down in A549 (adenocarcinoma) and H226 (squamous carcinoma) cells.…”
Section: High Expression Of Nrp1 Promotes Nsclc Metastasis In Vitromentioning
confidence: 91%
“…A previous study by the authors demonstrated that the expression of NRP1 was high in NSCLC tissues and was associated with a poorer survival of patients (22). In addition, NRP1 can promote NSCLC cell proliferation and migration via the EGFR signaling pathway (22). Taken together, it was thus hypothesized that dysregulated NRP1 can influence TGF-β1-induced EMT.…”
Section: Neuropilin 1 Modulates Tgf-β1-induced Epithelial-mesenchymalmentioning
confidence: 98%
See 1 more Smart Citation
“…MicroRNAs (miRs) represent a class of 21-23 nucleotides long small non-coding RNAs that can act as oncogenes (8) or tumor suppressors (9) in various types of cancer, including gastrointestinal (10), liver (11), pancreatic (12), ovarian (13), lung (14) and breast cancer (15). miRs can bind directly to the 3'-untranslated region (UTR) of target genes to negatively regulate protein expression (16).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that NRP1 is up-regulated in NSCLC tissues and associated with poorer survival in patients. Meanwhile NRP1 can promote NSCLC cells proliferation and migration via EGFR signaling pathway [22]. Taken together, we hypothesized that dysregualted NRP1 can influence TGF-β1-induced EMT.…”
Section: Introductionmentioning
confidence: 85%